Flow Stress Characteristics and Constitutive Modeling of Typical Ultrahigh‐Strength Steel under High Temperature and Large Strain. Issue 3 (16th November 2022) - Zhao, Mingjie; Huang, Liang; Li, Changmin; Su, Yang; Guo, Shiqi; Li, Jianjun; Sun, Chaoyuan; Li, Pengchuan
Abstract : Hot compression experiments are conducted to explore the deformation behaviors of 300M steel under large strain, which can mimic the forging process of large components. It is found that the variations of flow stress are affected by the deformation parameters and the rivalry between work hardening and dynamic softening. A novel constitutive model is proposed to forecast the flow stress at different deformation parameters. The Pearson correlation coefficient between the experimental flow stress and the predicted flow stress by the newly proposed constitutive model is 3.489%, and the relative error is within the range of ±5%. It implies that the newly proposed constitutive model can describe the variations of flow stress appropriately. Furthermore, the prediction accuracy of the newly proposed constitutive model is compared with that of the strain‐compensated Arrhenius constitutive model, the modified Johnson–Cook constitutive model, and the Hensel–Spittel constitutive model. Results demonstrate that the novel constitutive model provides the highest accuracy, followed by the strain‐compensated Arrhenius constitutive model, then the Hensel–Spittel constitutive model, and the modified Johnson–Cook constitutive model has the weakest accuracy. The establishment of the novel constitutive model is helpful in accurately predicting the flow behavior of materials during the forging process. Abstract : The flow characteristics of typical ultrahigh‐strength steel under high temperatures and large strains are analyzed. A novel constitutive model is proposed to describe the complex flow characteristics affected by strain, deformation temperature, and strain rate. The prediction accuracy of the newly proposed constitutive model is compared with those of different classic constitutive models.